Millennials and contraception: why do they forget? An international survey exploring the impact of lifestyles and stress levels on adherence to a daily contraceptive regimen. (2nd January 2019) - Caetano, Cecilia; Peers, Tina; Papadopoulos, Linda; Wiggers, Katja; Engler, Yvonne; Grant, Heather
Abstract: Background: Rates of unintended pregnancies are particularly high in young women, a finding that may be associated with their tendency not to use contraceptives correctly and/or consistently. For millennial women, busy lifestyles and associated stress may impact on daily activities including taking an oral contraceptive pill. Methods: Contraceptive pill users aged 21–29 years ('millennial' women; N  = 4500) from nine countries in Europe and North and South America completed an online questionnaire on their daily habits and activities, disruptions to their routine and associated stress levels. Results: Thirty-nine percent of surveyed participants had forgotten to take their contraceptive pill at least once in the past month; 39% also admitted not taking it at the same time each day. On average, participants had experienced two major disruptions to their daily lives in the past year, with three quarters (74%) believing these disruptions increased their stress levels. Of those who had missed at least one pill in the past year, 40% attributed it to a busy schedule and 21% to stress, among other reasons. Over half of respondents (55%) reported they were more likely to forget their pill when preoccupied. Conclusions: Times of stress may make it more likely for millennial women to forget to take their pill. Health care providers should be aware of typical contraceptive adherence rates among young women and ensure that contraceptive counselling sessions include discussion of lifestyle issues and potential barriers to adherence. Every woman should be counselled on all available methods, so that she can make an informed choice on what best suits her.